Mathematical Modeling of Microcirculation Disorders in the Human Circulatory System - Andreicheva, E. N.; Khramchenkov, M. G. (Lobachevskii journal of mathematics, 2024)
The work is devoted to mathematical modeling of microcirculation disorders in the human circulatory system based on the model of physical and chemical filtration of liquid in a deformable medium with double porosity. Thrombosis, sludge and embolism are considered as the main factors of microcirculation disorders. The substantiation of the possibility of using the proposed approach is considered. An exact solution in the simplest case to one-dimensional problem is obtained, and an analysis of the obtained solution is given.